Beauty Culture and Self-Commodification: Analysis of Visual Communication In Digital Content on Tiktok Social Media - Sela Aditia, Dinda; Nugroho, Catur (Economics and Business Journal (ECBIS), 2026)
This study aims to describe the following variables: (1) digital technology adoption, (2) business resilience, (3) women’s empowerment, and (4) financial literacy, and to analyze the effect of digital technology adoption on business resilience mediated by women’s empowerment and moderated by financial literacy. The research employed a quantitative explanatory design with structural model analysis using Partial Least Squares Structural Equation Modeling (PLS-SEM). Data were collected through an online questionnaire (Google Form). The population consisted of 1,556 women entrepreneurs who own Micro and Small Industry (MSI) units in the food subsector, with 359 respondents selected using proportionate allocation sampling and located in Tasikmalaya, Sukabumi, Bogor, and Bandung. The findings indicate that the level of digital technology adoption among women entrepreneurs is in the very high category, while business resilience, women’s empowerment, and financial literacy are in the high category with potential for further improvement. Digital technology adoption has a positive effect on business resilience and women’s empowerment, implying that higher levels of technology adoption are associated with stronger business resilience and greater women’s empowerment. Women’s empowerment also positively affects business resilience and mediates the relationship between digital technology adoption and business resilience. In addition, higher financial literacy strengthens the effect of digital technology adoption on business resilience, thus functioning as an enhancing moderator in this relationship. The results imply that strengthening business resilience among women entrepreneurs can be achieved by enhancing digital technology–based resources and strategies, integrated with women’s empowerment as a mediating mechanism and financial literacy as a moderating capability for the strategic use of digital technology. Practically, the findings underscore the importance of advanced training programs and an integrated digital ecosystem to reinforce digital technology adoption, women’s empowerment, and financial literacy, while simultaneously building a collaborative ecosystem and continuous interventions focused on sustainable business resilience.